Maintenance Management of Office Facilities and Infrastructure at Temmalebba Village Office, Palopo City (Pinisi Journal of Officers Review, 2024)
. Office infrastructure is included in an important component in an organization and sometimes even people assess the quality of an office service by paying attention to adequate, good and complete and modern facilities so that it is considered a quality office. This study focuses on knowing how to manage the maintenance of office facilities and infrastructure at the Temmalebba Village Office, Palopo City. Therefore, research has a significant role in identifying maintenance management activities for office facilities and infrastructure. This research is qualitative, therefore to achieve the research objectives some of the indicators used in this study are considered not to have run optimally based on the results of the study. Data collection methods used include documentation, interviews and observations. The indicator in question is maintenance planning that has been carried out by making inventory books, making maintenance schedules, and following up on items to be inventoried to the removal process. Then at the stage of carrying out maintenance, routine maintenance has been carried out even though it has not been effective, periodic maintenance and cleaning once a week, maintenance of the machine both before it is damaged and has been damaged. Followed by the supervision stage carried out by subordinates to superiors and within the scope of the village itself then reported to the sub-district and followed up by the asset field of BPKAD Palopo City for direct visits to the village office. After that, the evaluation stage, although only carried out orally, becomes an improvement material for better care and maintenance. This study presents new information by linking detailed theories and research loci different from previous research on maintenance management of office facilities and infrastructure so that it can be used as evaluation material for research loci to improve the implementation of maintenance management of office facilities and infrastructure.